Practical training report in competency management section of human resource management department in Wisma Bapa Malaysia / Awang Nasfuddin Awang Hassan - Awang Hassan, Awang Nasfuddin (Universiti Teknologi MARA, Sarawak, 2011)
Sarawak State Civil Service is closely related with the establishment of Sarawak State Assembly as the oldest legislative body in Malaysia. The assembly has been in existence since 8 September 1867 during the first meeting at Bintulu. On 8 September 1867 the legislators consist of 21 council members led by Raja Charles Brooke. 6 of Brooke’s officers and local leaders were also involve in the meeting. In the year 1903, the assembly was renamed as State Council and just before the war in 1941, Prince Brooke Vyner has established written constitution and during the 100 years of Brooke administration in Sarawak, the membership of the council has increased to 24 members. The King’s position has been replaced by the Chief Secretary as the chairman. The numbers of council members keep on increasing from 1963 to 2006 where it has reached a total of 71 council members. In 1976, the State Council has been renamed as State Legislative Council. Chief Minister’s Department is at Wisma Bapa Malaysia. The building was officiated on 17 August 1976 and taking the name of the first Prime Minister of Malaysia, Tunku Abdul Rahman Putra Al Haj as the “Father of Independence”. Besides the Chief Minister’s Office, the building also accommodates two Deputy Chief Ministers, young ministers, and State high ranking officers such as the State Secretary, State Finance Secretary, State Attorney General, and directors from various units and departments under the supervisions of Chief Minister Department.